KNOWLEDGE FACTORS OF KNOWLEDGE-SHARING INTENTION AND BEHAVIOR - Mahyarni mahyarni; M. S. Idrus; Fatchur Rohman; Noermijati noermijati (APMBA (Asia Pacific Management and Business Application), 2012)
Changes in the external environment in the world of education, ranging from the social, economy, technology, and politics, require a rethinking of these influences as an institution and  their interactions. Islamic University has more challenges than other high education. The challenges are linked to the human resource improvement in science and technology. Islamic University has also been bonded to a commitment in leading the core mission of university; therefore, Islamic University has to hold strong commitment and needs to be attached by a self-image which bolds life values in leading the commitment. This research is based on the theory of reasoned action and the theory of planned behavior, which develops other theories related to knowledge-sharing behavior such as covering information technology and Islamic teachings. Data are analyzed using Structural Equation Modeling with Analysis of Moment Structures application program. The research objectives are to test and analyze direct and indirect effects of information technology covering variables, Islamic teachings, attitude, subjective norm and perceived behavior control and knowledge-sharing behavior.The result shows that technology, religion taught, and theory of planned behavior insignificantly influence knowledge-sharing behavior.